Evaluating the use of adjuvant and neoadjuvant terminology in bariatric surgery: a scoping review - Sher, Theo; McGee, Michelle; DuCoin, Christopher; Sujka, Joseph; Docimo, Salvatore (Journal of gastrointestinal surgery, 2024)
Weight regain and inadequate weight loss are common after bariatric surgery. Literature is emerging regarding the use of pharmacotherapy with bariatric surgery as a potential solution to these adverse effects. Pharmacotherapy may be used before (neoadjuvant) or after (adjuvant) bariatric surgery, although this terminology has not been standardized. As a rapidly growing area of research, there is opportunity to standardize terminology for future ease of research, data synthesis, and communication. This review aimed to comprehensively evaluate the use of the terms “adjuvant” and “neoadjuvant” to describe pharmacotherapy used in combination with bariatric surgery and propose standardized terminology for future research. Literature search was conducted systematically and in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were included if they were published after 1999; were randomized controlled trials, prospective/retrospective cohort studies, or case series; and used human subjects that were adults at least 18 years of age. The use of the terms “neoadjuvant” and “adjuvant” was analyzed over time. Thirty-four publications were included. Thirty-two (94.1%) studied the use of adjuvant pharmacotherapy after bariatric surgery. Four (11.8%) studied the use of pharmacotherapy before bariatric surgery, and 1 used the term “neoadjuvant” to describe medications used before bariatric surgery. Eight publications used the term “adjuvant” to describe medications used after bariatric surgery. Standardized terminology is needed to ease future understanding, evidence synthesis, and dissemination of work. We propose that the terms “neoadjuvant” and “adjuvant” become the standard terminology to describe pharmacotherapy use before and after bariatric surgery, respectively.